Co-Constructing a Community-Based Telemedicine Program for People With Opioid Use Disorder During the COVID-19 Pandemic: Lessons Learned and Implications for Future Service Delivery - Stine Bordier Høj; Catherine de Montigny; Sofiane Chougar; Robert Léandre; Marie-Ève Beau; Geneviève Boyer-Legault; Amélie Goyette; Sara-Kim Lamont; Julie Bruneau (JMIR Publications, 2023)
The COVID-19 pandemic triggered unprecedented expansion of telemedicine, including in the delivery of opioid agonist treatment (OAT) for people with opioid use disorder (OUD). However, many people with OUD lack the technological resources necessary for remote care, have complex needs, and are underserved, with precarious access to mainstream services. To address the needs of these individuals, we devised a unique program to deliver OAT via telemedicine with the support of community outreach workers in Montreal (Quebec, Canada). The program was co-constructed by the service de médecine des toxicomanies of the Centre hospitalier de l'Université de Montréal (CHUM-SMT)-a hospital-based addiction medicine service-and CACTUS Montréal-a community-based harm reduction organization known and trusted by its clientele. All procedures were jointly developed to enable flexible and rapid appointment scheduling. CACTUS Montréal workers promoted the program, facilitated private on-site telemedicine connections to the CHUM-SMT, accompanied patients during web-based appointments if requested, and provided ongoing holistic support and follow-up. The CHUM-SMT offered individualized OAT regimens and other health services as needed. Overall, our experience as clinicians and community-based workers intimately involved in establishing and running this initiative suggests that participants found it to be convenient, nonjudgmental, and responsive to their needs, and that the implication of CACTUS Montréal was highly valued and integral to patient engagement and retention. Beyond the context of the COVID-19 pandemic, similar programs may present a flexible and accessible means to deliver alternative treatment options for people with OUD disengaged from traditional care, bridge gaps between communities and health providers, and improve access to care in rural or remote settings.